2015
DOI: 10.4068/cmj.2015.51.2.86
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Smoking and Its Impact on Treatment Outcomes in Newly Diagnosed Pulmonary Tuberculosis Patients: A Hospital-Based Prospective Study

Abstract: There is growing evidence that tobacco smoking is an important risk factor for tuberculosis (TB). India, with a population of 1.26 billion, has the highest number of both TB patients and smokers. The convergence of these two important health hazards is likely severely affecting India's TB control programs. This study was carried out to determine the prevalence of smoking in newly diagnosed pulmonary TB patients and the impact of smoking on disease outcomes in a tertiary care hospital. All patients newly diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
48
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 12 publications
8
48
1
6
Order By: Relevance
“…In our patients, in addition to severe clinical manifestations of the disease, poorer treatment outcomes and relapse were significantly more frequent. This is consistent with other studies, where relapse of TB was recorded in 10.4% of patients [30]. For example, in a survey conducted in Georgia, smokers had a 70% poorer outcome than nonsmokers [22].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our patients, in addition to severe clinical manifestations of the disease, poorer treatment outcomes and relapse were significantly more frequent. This is consistent with other studies, where relapse of TB was recorded in 10.4% of patients [30]. For example, in a survey conducted in Georgia, smokers had a 70% poorer outcome than nonsmokers [22].…”
Section: Discussionsupporting
confidence: 92%
“…For example, in a survey conducted in Georgia, smokers had a 70% poorer outcome than nonsmokers [22]. Patients experiencing extensive changes on the lung parenchyma often suffer from relapses and are at increased risk of mortality [29,30]. Among our patients, there were more death outcomes in smokers suffering from TB.…”
Section: Discussionmentioning
confidence: 79%
“…Around 28% (8/29) of the TB cases reported being current smokers and a similar proportion (5/18) indicated that they did smoke in the past. This is higher than that reported in another study among Hajj pilgrims with TB (13.3%) [7] but lower than figures from some international reports [15,16]. Other risk factors for TB such as visit to, or residence in high-burden countries and occupational exposure were uncommon among TB patients in the study and so was previous Hajj or Umrah performance.…”
Section: Discussioncontrasting
confidence: 68%
“…Eight studies were conducted in urban areas and two in rural areas (Table K in S4 Text). All of the studies are high-quality with regard to sampling strategy; however, two of the studies did not report the proportion of the cohort that was lost to follow-up during the study period [72,73]. Two of the studies describing TB outcomes among HIV-infected individuals are very low in quality because they have a sample size of <100 patients (Table K in S4 Text) [51,74].…”
Section: Resultsmentioning
confidence: 99%